(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Axial spondylitis (AxSpA) is traditionally considered a chronic inflammatory disease primarily affecting the axial skeleton. However, in recent years, its extraskeletal manifestations, including nervous system involvement in the form of cognitive impairment and neuroinflammation, have attracted the attention of researchers. In AxSpA , these manifestations are underpinned by a multifactorial pathogenesis: systemic and neuroinflammation, chronic pain, sleep disturbance, comorbid depression and anxiety, and the impact of drug therapy. The aim of this review is to summarize current data on the prevalence, pathogenesis, clinical significance of cognitive impairment, and the role of neuroinflammation in AxSpA.